Pengaruh Layanan Food Delivery Pada Aplikasi Gojek Terhadap Keputusan Pembelian Pada Mahasiswa Universitas Negeri Medan - Imamul Khaira; Zulkarnain Siregar; Hasiandra Simanjuntak; Putri Sandrina Sitompul (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to determine the effect of food delivery on the Gojek application on purchasing decisions. This research explains whether food delivery services will influence purchasing decisions and increase buyer loyalty. In this research, we use simple regression analysis to show how influential variable x on variable y where before carrying out the analysis we carried out several tests such as normality, linearity and correlation tests to ensure our data was valid or not. From the results of the research it shows that there is an influence of Gojek food delivery services on purchasing decisions which from the analysis we carried out shows that the existence of food delivery services helps consumers in purchasing food. The conclusion we can draw is that variable of the large number of consumers who use the Gojek application to buy food due to discount time factors, etc